Modeling of the transition from transgranular to intergranular fracture at elevated temperatures in EI698 nickel alloy (Fracture and Structural Integrity, 2025)
In this study, an efficient computational method for modeling the transition from transgranular to intergranular fracture mechanisms based on phase field fracture theory is discussed. Structural heterogeneity of the material is modeled on the basis of Voroni diagrams. Parameters characterizing the mechanical properties of the material for the intergranular and transgranular space are the same for models of continuum mechanics. The location of crack initiation and the crack path in the proposed method controlled by the difference in the values of the critical energy release rate for the intergranular and transgranular spaces for the phase field model. The source code of the created and used finite element is an open source project and available to download from https://github.com/Andrey-Fog/ANSYS-USERELEMENT-PHFLD. The obtained results correlate well with previously conducted fractographic studies.
Keywords: Granular structure; Phase field fracture; Transgranular fracture; Intergranular fracture